Knowledge, Attitudes, or Normative Beliefs: What Matters When Teachers Want to Teach Geography Competency-Based? - Horn, Michael; Schweizer, Karin; Götz, Kristina; Krauß, Benjamin (Journal of Geography Education, 2017)
Teachers of geography appear to possess a good knowledge of how to teach in a competency-based manner but they hardly act upon that knowledge when teaching. To address this gap between theory and practice, a study was conducted involving 60 geography teachers from German secondary schools. The extent to which the geography teachers’ intentions to teach competency-based could be predicted by their attitudes towards and normative beliefs about competency-based teaching was assessed. Furthermore, the interplay of those predictors with knowledge about competency-based teaching of geography and teacher’s age was examined. In this sample, a wide range of knowledge and differing attitudes towards teaching geography in a competency-based manner was found. This group of teachers also differed widely in terms of their intentions to teach geography competency-based within the next school year. The teachers’ age had an influence on both the intentions as well as the knowledge of competency-based teaching. Age was also negatively correlated with both attitudes towards and normative beliefs about teaching geography in a competency-based way. Age, knowledge, attitudes and normative beliefs were all predictors of teachers’ intentions to teach geography in a competency-based manner, explaining 79% of the variance. However, only attitudes towards competency-based teaching of geography predicted variance in intentions, even after the effects of age, knowledge and normative beliefs were controlled for. This suggests that teachers’ attitudes towards teaching geography competency-based significantly influence their intentions to use this teaching approach. Other factors, which might explain the variance that could not be accounted for, are discussed.